When East meets West: comparing the utilization of high‐performance work systems in Chinese and Irish professional service firms. (12th November 2015) - Fu, Na; Ma, Qinhai; Flood, Patrick C; Bosak, Janine; Liu, Yang; Zhang, Yang
Abstract : The aim of this study was to explore the differences and similarities in the utilization of high‐performance work systems (HPWS) in Chinese and Irish professional service firms (PSFs). Using data collected from 112 Chinese and 120 Irish accounting firms, we found that Chinese PSFs demonstrate higher scores in selective recruitment and contingent remuneration, while Irish PSFs show higher scores in performance management and training. Chinese and Irish PSFs employed similar levels of information sharing and participation and had similar scores on an overall HPWS index. Consistent results were found for the positive relationship between HPWS and organizational performance in both Chinese and Irish PSFs despite their different utilization of HPWS elements. This cross‐national study provides insights into the differences between eastern and western approaches in managing human resources in the professional service context and demonstrates the potential value of using HPWS to improve performance in PSFs. Key points: There were some differences and some similarities in the utilization of high‐performance work systems (HPWS) in Chinese and Irish professional service firms (PSFs). Chinese PSFs demonstrated higher scores in selective recruitment and contingent remuneration while Irish PSFs showed higher scores in performance management and training. Chinese and Irish PSFs had similar scores in information sharing and participation as well as in an overall HPWS index. Despite the different utilization of HPWS elements, a positive relationship between HPWS and organizational performance was found in both Chinese and Irish PSFs.